2016
DOI: 10.18632/oncotarget.14297
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ALDH2 by O-GlcNAcylation contributes to the hyperglycemic exacerbation of myocardial ischemia/reperfusion injury

Abstract: Although hyperglycemia is causally related to adverse outcomes after myocardial ischemia/reperfusion (I/R), the underlying mechanisms are largely unknown. Here, we investigated whether excessive O-linked-N-acetylglucosamine (O-GlcNAc) modification of acetaldehyde dehydrogenase 2 (ALDH2), an important cardioprotective enzyme, was a mechanism for the hyperglycemic exacerbation of myocardial I/R injury. Both acute hyperglycemia (AHG) and diabetes (DM)-induced chronic hyperglycemia increased cardiac dysfunction, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Furthermore, we found that daidzin (an ALDH2 antagonist) abolished baicalin‐exhibited beneficent effects against H/R‐induced cytotoxicity and apoptosis in H9c2 cells, and Alda‐1 (an ALDH2 agonist) also reversed H/R‐induced cytotoxicity and apoptosis. These results were in accordance with these studies whereby the modulation of ALDH2 activity by daidzin or Alda‐1 could affect myocardial apoptosis caused by I/R or H/R injury in isolated hearts and in cells . These results suggested that enhancing of ALDH2 activity and expression mediated H/R injury and the protective effects of baicalin against H/R injury in H9c2 cells.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, we found that daidzin (an ALDH2 antagonist) abolished baicalin‐exhibited beneficent effects against H/R‐induced cytotoxicity and apoptosis in H9c2 cells, and Alda‐1 (an ALDH2 agonist) also reversed H/R‐induced cytotoxicity and apoptosis. These results were in accordance with these studies whereby the modulation of ALDH2 activity by daidzin or Alda‐1 could affect myocardial apoptosis caused by I/R or H/R injury in isolated hearts and in cells . These results suggested that enhancing of ALDH2 activity and expression mediated H/R injury and the protective effects of baicalin against H/R injury in H9c2 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Emerging evidence show the beneficial impact of ALDH2 on ischaemia and reperfusion injuries . Hence, to further explore whether ALDH2 is involved in the protective effects of baicalin against H/R injury, we then demonstrate the effects of baicalin on ALDH2 level and activity in H9c2 cells.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…We have a longstanding interest in the effects of ALDH2 and the cardiovascular system 24, 25, 26. We previously found that ALDH2 activation by Alda‐1 reduced the senescence phenotype in H9C2 cell lines 23.…”
Section: Resultsmentioning
confidence: 99%